Modeling of the radioactive situation in contaminated zone - Применко, В.І.; Канунніков, Б.Т.; Жижченко, О.П.; Лук’янчиков, В.А. (Proceedings of National Aviation University (archive), 2004)
Calculation of decreasing of radionuclide activity as the function of the distance. The equation for calculation of decreasing the level of radiation and activity of radionuclide as a function of distance to destroyed atomic reactor is given. The term of one-kilometers zone – the territory from which the calculation of decreasing the radionuclide activity is initiated – is introduced.